2011
DOI: 10.1002/em.20694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Comet assay dose‐response for ethyl methanesulfonate using freshly prepared versus cryopreserved tissues

Abstract: The National Toxicology Program (NTP) is using the Comet assay to evaluate genotoxic potential, and is investigating the integration of this assay into repeat-dose toxicity studies. To reduce sample-to-sample variability, address logistical concerns associated with evaluating multiple tissues from many animals, and accommodate sample collection at geographically distant testing facilities, tissue samples collected for Comet analysis by the NTP are routinely flash-frozen in liquid nitrogen and stored in a -80°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Slides were prepared and analyzed as described previously (Hobbs et al ; Recio et al ) with some modifications. In a laboratory with controlled humidity (≤60%), samples were thawed on ice and a portion of the cell suspension was diluted with 0.5% low melting point agarose (Lonza, Walkersville, MD) dissolved in Dulbecco's phosphate buffer (Ca +2 , Mg +2 , and phenol free) at 37°C and layered onto each well of a 2‐well CometSlide™ (Trevigen, Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Slides were prepared and analyzed as described previously (Hobbs et al ; Recio et al ) with some modifications. In a laboratory with controlled humidity (≤60%), samples were thawed on ice and a portion of the cell suspension was diluted with 0.5% low melting point agarose (Lonza, Walkersville, MD) dissolved in Dulbecco's phosphate buffer (Ca +2 , Mg +2 , and phenol free) at 37°C and layered onto each well of a 2‐well CometSlide™ (Trevigen, Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Except for stomach, the fold increase in % tail DNA values was generally lower in cell suspensions that were frozen before slide processing; however, the increase was always statistically significant. Although our results are from a limited number of studies, others have investigated the effect of freezing cell suspensions and subsequent transportation by air courier (Recio et al, 2012). Consistent with our results, they observed that the % tail DNA in liver, blood and stomach from control and EMS-treated rats was increased relative to tissues processed immediately by freezing the cells for 1-8 weeks prior to slide preparation but the level was still within the negative control background 1-8% recommended by JaCVAM.…”
Section: Effect Of Freezing On % Tail Dnamentioning
confidence: 99%
“…Cells frozen with DMSO (blood cells or cell lines) have previously been used for comet assay validation (2,7–15). Effect of freezing tissues as cell suspensions frozen in 10% DMSO was investigated using rats exposed by repeated oral gavage to ethyl methanesulphonate (16). DNA strand break levels in fresh and frozen blood, liver and stomach samples were similar at all exposure levels collected 3h after exposure, even in tissues that had undergone transportation.…”
Section: Discussionmentioning
confidence: 99%